Inherent Mosaicism and Extensive Mutation of Human Placentas. Issue 6 (June 2021) - Coorens, Tim H. H.; Oliver, Thomas R. W.; Sanghvi, Rashesh; Sovio, Ulla; Cook, Emma; Vento-Tormo, Roser; Haniffa, Muzlifah; Young, Matthew D.; Rahbari, Raheleh; Sebire, Neil; Campbell, Peter J.; Charnock-Jones, D. Stephen; et al.
Abstract : (Abstracted from Nature 2021;592:80–85) Approximately 1% to 2% of pregnancies involve chromosomal aberrations confined to the placenta. During the first few days of embryogenesis when fetal and placental lineages diverge, clonal expansion and mosaicism may occur, representing a potential pathological divergence from normal clonal dynamics of early embryogenesis.